Synchronous Aberrant Cerebellar and Opercular Development in Fetuses and Neonates with Congenital Heart Disease: Correlation with Early Communicative Neurodevelopmental Outcomes, Initial Experience - Wong, A.; Chavez, T.; O'Neil, S.; Votava-Smith, J.; Miller, D.; delCastillo, S.; Panigrahy, A.; Paquette, L. (American Journal of Perinatology Reports, 2017)
Patients with congenital heart disease (CHD) demonstrate multidomain cognitive delays. Cingulo-opercular and cerebellar brain networks are critical to language functions. This is a description of our initial experience aiming to identify an anatomic correlate for CHD patients with expressive language delays. Fetal CHD patients, prospectively enrolled, underwent serial fetal (1.5T), postnatal pre- and postoperative (3T) MRI. Non-CHD patients were enrolled retrospectively from the same epoch. Comparable fetal and neonatal T2 contrast was used for manual linear cross-sectional measurement. Multivariable analysis was used for adjustments and curve fitting. Neurodevelopment was assessed with Battelle Developmental Inventory, 2nd ed. between 9 and 36 months of age. This interim analysis included patients from our longitudinal CHD study who had fetal, postnatal imaging and neurodevelopmental data—yielding a total of 62 mothers (11 CHD fetuses and 51 non-CHD fetuses). Altered brain trajectories were seen in selected cerebellar and opercular measurements in CHD patients compared with the non-CHD group. Smaller inferior cerebellar vermis measurements were associated with multiple communication-related abnormalities. Altered early structural development of the cerebellum and operculum is present in patients with CHD, which correlates with specific neurodevelopmental abnormalities.
Keywords: congenital heart disease; fetus; neonate; brain growth; neurodevelopment; communication